Identification of Ion Channel-Related Genes and miRNA-mRNA Networks in Mesial Temporal Lobe Epilepsy - Su, Zhengwei; Li, Yinchao; Chen, Shuda; Liu, Xianyue; Zhao, Ke; Peng, Ying; Zhou, Liemin (Frontiers in Genetics, 2022)
Objective: It aimed to construct the miRNA-mRNA regulatory network related to ion channel genes in mesial temporal lobe epilepsy (mTLE), and further identify the vital node in the network. Methods: Firstly, we identified ion channel-related differentially expressed genes (DEGs) in mTLE using the IUPHAR/BPS Guide to Pharmacology (GTP) database, neXtProt database, GeneCards database, and the high-throughput sequencing dataset. Then the STRING online database was used to construct a protein-protein interaction (PPI) network of DEGs, and the hub module in the PPI network was identified using the cytoHubba plug-in of Cytoscape software. In addition, the Single Cell Portal database was used to distinguish genes expression in different cell types. Based on the TarBase database, EpimiRBase database and the high-throughput sequencing dataset GSE99455, miRNA-mRNA regulatory network was constructed from selected miRNAs and their corresponding target genes from the identified DEGs. Finally, the rats were selected to construct chronic li-pilocarpine epilepsy model for the next stage experimental verification, and the miR-27a-3p mimic was used to regulate the miRNA expression level in PC12 cells. The relative expression of miR-27a-3p and its targeting mRNAs were determined by RT-qPCR. Results: 80 mTLE ion channel-related DEGs had been screened. The functional enrichment analysis results of these genes were highly enriched in voltage-gated channel activation and ion transport across membranes. In addition, the hub module, consisting of the Top20 genes in the protein-protein interaction (PPI) network, was identified, which was mainly enriched in excitatory neurons in the CA3 region of the hippocampus. Besides, 14 miRNAs targeting hub module genes were screened, especially the miR-27a-3p deserving particular attention. miR-27a-3p was capable of regulating multiple mTLE ion channel-related DEGs. Moreover, in Li–pilocarpine-induced epilepsy models, the expression level of miR-27a-3p was increased and the mRNAs expression level of KCNB1, SCN1B and KCNQ2 was decreased significantly. The mRNAs expression level of KCNB1 and KCNQ2 was decreased significantly following PC12 cells transfection with miR-27a-3p mimics. Conclusion: The hub ion channel-related DEGs in mTLE and the miRNA-mRNA regulatory networks had been identified. Moreover, the network of miR-27a-3p regulating ion channel genes will be of great value in mTLE.